THE TRADITION OF TEPUNG TAWAR IN THE PERSPECTIVE OF CONTEMPORARY ISLAMIC RELIGIOUS EDUCATION - Agustina, Agustina; Mahrus, Erwin; Purwanti, Nopi (Khatulistiwa, 2025)
The Tepung Tawar tradition is one of the cultural ceremonies still preserved by the Malay community, including in Sambas Regency, West Kalimantan. This ceremony is usually performed to mark significant events in a person's life, such as weddings, births, or other major occasions. The aim of this research is to describe and explain the Tepung Tawar tradition practiced among the people of Sambas. This study falls under the qualitative cluster with an ethnographic approach. Data collection was carried out through observation, interviews, and documentation. Data analysis was conducted through data condensation, data display, and drawing conclusions. The results of this study show that the Tepung Tawar tradition in Sambas, West Kalimantan, is a cultural heritage that has deeply rooted within the local community. Typically performed during important moments such as weddings or births, this ceremony involves the pouring of rice fowder and prayer water on the celebrated individual, symbolizing blessings and prayers for safety. From the perspective of contemporary Islamic religious education, this tradition reflects the practice of social and spiritual values that harmonize with Islamic teachings. Although not a core part of Islamic teachings, the Tepung Tawar practice can be understood as an effort to strengthen brotherhood and maintain a balance between culture and religion in community life.